Species composition analysis of shrub- and canopy layer data of spontaneous habitats in Cserhát Hills - Zagyvai, Gergely (JOURNAL OF LANDSCAPE ECOLOGY, 2024)
Characteristics of species composition and determining background factors were studied based on data of shrub and canopy layer in spontaneous habitats. Secondary succession processes were evaluated in aspect of plant invasion risk and regeneration ability in sample parcels of Cserhát Hills (North Hungary). Canopy, shrub layer data and potential background factors of spontaneous habitats were analysed by principal component analysis (PCA) and canonical correspondence analysis (CCA). Shrub spreading on abandoned arables and pastures are determined by thorny species (Crataegus monogyna, Prunus spinosa, Rosa canina). These shrublands can develop to forests with participation of Quercus cerris and Pyrus pyraster, if supporting species sources are given. Spreading of Ligustrum vulgare and Cornus sanguinea is typical for abandoned vineyards and orchards. Some relict fruit tree species of old agriculture stay active component of succession: Juglans regia with significant allelopathic effect; domestic Prunus taxa with effective capacity forming root suckers. One of the most common scenario of abandoned parcels in this landscape is the spreading of invasive Robinia pseudoacacia and become closed forest. Variables describing the vegetation environment of the parcels are the most important from the examined 9 background factors. Age of the abandoned parcels is also notable variable, but it does not mean definitely the closing of the canopy as time goes on. Shrub and tree spreading is blocked in steeper, dry, strong irradiated hillsides. These conditions and sites provide habitat for some rare, valuable shrub species (Colutea arborescens, Berberis vulgaris, Rhamnus cathartica, Rosa spinosissima) of the landscape.
Keywords: secondary succession; regeneration; plant invasion; propagule source; ecological factors